Risk Factors for Very Preterm Births in French Guiana: The Burden of Induced Preterm Birth - Leneuve-Dorilas, Malika; Favre, Anne; Louis, Alphonse; Bernard, Stéphanie; Carles, Gabriel; Nacher, Mathieu (American Journal of Perinatology Reports, 2019)
Background Early preterm births are still represented as a major public health problem in French Guiana. The objective of the present study was to study factors associated with early preterm birth in French Guiana.Methods A monocentric age-matched case control study was conducted at the sole level 3 maternity in French Guiana. In utero fetal deaths and multiple pregnancies were not included. Cases were defined as giving birth prematurely between 22 and 32 weeks of pregnancy. Controls were defined as women delivering on term. For each case three controls were matched on age. In utero deaths, medical pregnancy interruptions and multiple pregnancies (a known major cause of preterm delivery) were excluded from the study. Sociodemographic variables, medical and obstetrical history, the complications of the current pregnancy, and the results of the last vaginal swab before delivery were recorded in the second or the third trimester. Thematic conditional logistic regression models were computed.Results Overall 94 cases and 282 matched controls were included. Preterm delivery was spontaneous in 47.9% (45/94) of the cases and induced in 52.1% (49/94).A history of preterm birth was associated with both spontaneous and induced preterm delivery. The absence of health insurance was associated with spontaneous early preterm delivery AOR (adjusted odd ratio) = 9.1 (2.2–38.3), p = 0.002 but not induced preterm delivery adjusted odd ratio (AOR) = 2.1 (0.6–6.7), p = 0.2. Gravidic hypertension, placenta praevia, intrauterine growth retardation and mostly preeclampsia (66%, 32/49) were linked to induced preterm delivery but not spontaneous delivery. Gardnerellavaginalis and group B Streptococcus infections were significantly associated with induced early preterm delivery but not spontaneous early preterm delivery.Conclusions Social factors were associated with spontaneous early preterm delivery, suggesting that efforts to reduce psychosocial stressors could lead to potential improvements. Vaginal infections were also associated with induced preterm labor suggesting that early diagnosis and treatment could reduce induced early preterm delivery. Preeclampsia was a major contributor to induced early preterm delivery. Reliable routine predictors of preeclampsia are still not available which makes its prevention impossible in first pregnancies.
Keywords: preterm delivery; preeclampsia; vaginosis; social stressors; access to care